Peran Metode Pengajaran Hadis pada Madrasah Salaf dalam Mewujudkan Sikap Moderat - Nurudin, Muhamad; Partono, Partono; Masruri, Muhammad; Faza, Izah Q. (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This research is motivated by the emergence of experts' opinions that Salaf madrasas have a radical understanding of Hadith, so that the institution is known to be a cadre of radical or fundamental santri. In fact, not all Salaf madrasas have radical thinking. In fact, they are known as moderate madrasas, so they educate their students to have a moderate attitude in religion. The method of teaching hadith in salaf madrasas uses certain books, such as the book Bulughul Maram. The role of an ustaz is very urgent in instilling attitudes to students, because it becomes the role model of the students. Through the teaching methods carried out by the ustaz, students will gain knowledge that becomes a reference in their behavior. There are two forms of Hadith understanding; textual and contextual. Textual understanding will give birth to a radical attitude in life. While contextual understanding fosters a moderate attitude in religion. Because of its vital position in front of the santri, the tendency of the ustaz's method of understanding will shape the attitude and personality of a santri. The results of the study state that the teaching method in Salaf Madrasah plays an important role in instilling a moderate attitude of the students, including: using comprehensive teaching, related to the identity of the institution or madrasah